MODEL OF DECISION SUPPORT SYSTEM USED FOR ASSESSMENT OF INSURANCE RISK - Rusov, Jelena S (Journal of Applied Engineering Science, 2016)
In order to run a modern business in uncertain times, business forcasting is very important for evaluation of company’s future financial performance. This paper shows an example of premium forecast based on the assessment of risk sources in insurance system. Due to uncertainty that is one of the characteristics of loss occurrence and indemnity amount, it is important to hold sufficient assets to cover the risk. For asset-liability matching, one should first assess the impact of risk on premium movement per insurance lines. This is the main concept of development and performance of insurance companies. This paper shows an experimental research of risk ranking based on projected model of decision support system. Decision support system is used with the aim to generate hierarchy of influential criteria and alternatives of risk assessment model for stated insurance lines. Suggested model supports the idea according to which one should first determine insurance lines with the highest risk and then, on that basis, make a decision on premium amount in the following period.